FACILITATING CLINICAL EDUCATION IN MEDICAL AND HEALTH PROFESSION EDUCATION - Sari, Sylvia Mustika; Ramani, Subha; Emilia, Ova; Suhoyo, Yoyo (Universitas Gadjah Mada, 2023)
Background: The clinical supervisor's roles influence the quality of clinical education as a teacher and their interaction with students. Underlined the importance of refreshment on clinical teaching skills for clinical supervisors, the 3rd Webinar series of IAMHPE has inspired the recommendations on essential elements in the clinical education of medical and health profession education.Gaps: Recent studies have highlighted the complexity of facilitating clinical education and the socio-cultural influence on clinical supervisor-student relations. As a gap, Indonesia has a hierarchical and collectivist culture and thus the potential to hinder improving students' learning development during clinical education.Recommendation: An understanding of the Gaps between literature and Indonesia's socio-cultural influence on clinical education, we develop several recommendations, including 1) Building Clinical Supervisor-Student Relations that support students' development; 2) Making role modeling explicit and integrating into teaching and learning;3) Facilitating the gradual development of students' clinical abilities, and 4) Re-conceptualization of feedback in clinical education as a “dialogue”.